Military, political, administrative and economic activities of general G.A. Emanuel in the Caucasus (1826–1831) - Asker V. Khashirov (Кавказология, 2022)
The article handles the military-political and administrative-economic activity aspects of General G.A. Emanuel as commander of the troops on the Caucasian line, in the Black Sea and Astrakhan, head of the Caucasian region. His contribution to the settlement of interethnic relations in the Central Caucasus is indicated. G.A. Emanuel preferred to use diplomatic methods instead of military punitive methods, whereby several ethnic groups voluntarily became part of the Russian Empire. But, against the Circassians of the Western Caucasus on his instructions, military punitive expeditions were conducted. Activities of G.A. Emanuel had a significant impact on the situation of Central Caucasus peoples: he organized the bringing of some peoples into the citizenship of the Russian Empire and established their political and administrative integration into the Russian Empire. In the process of administrative practice, he organized and conducted the first military scientific expedition to Elbrus in 1829. It can be concluded that the actions of G.A. Emanuel were aimed at integrating the peoples of the Caucasus with the Russian Empire in more civilized ways than those who held this position before and after him.